Clinical Features in Children with Posterior Polymorphous Corneal Dystrophy. Issue 4 (April 2017) - Ahn, Ye Jin; Choi, Soon Il; Yum, Hae Ri; Shin, Sun Young; Park, Shin Hae
ABSTRACT: Purpose: To describe clinical features in children diagnosed with posterior polymorphous corneal dystrophy (PPCD) in their first or second decade of life. Methods: A retrospective study was performed with the medical records of seven unrelated Korean pediatric patients who were diagnosed with PPCD and were followed up for a minimum of 3 years. Thorough ocular examinations were performed, including best-corrected visual acuity, intraocular pressure, refractive and keratometric measurements, slit-lamp biomicroscopy, and specular microscopy at all visits. Results: Slit-lamp examinations revealed vesicular lesions in one patient and horizontally parallel band-like endothelial lesions in six patients. Unilateral corneal involvement was displayed in 4 patients, yielding 10 eyes with deep corneal features characteristic of PPCD. Other corneal, iris, or fundus pathologic findings were not detected in all cases. Among four children who were examined in their visual development (approximately under 8 years of age), two cases demonstrated unilateral amblyopia at initial examination and exhibited improved visual acuity after refractive correction and occlusion therapy. Astigmatism more than 1.5D, which is generally considered amblyogenic, was found in 8 among 10 PPCD-affected eyes. A final visual acuity of more than 20/32 was achieved with appropriate refractive correction in all PPCD-affected eyes. There was a negative correlation between the corneal astigmatism and the mean endothelial cell density (ECD) ( r = −0.655, P = .011). Initial specular microscopic examinations revealed reduced ECD (1733.0 ± 543.9 cells/mm 2 ) composed of enlarged cells (average cell area, 624.8 ± 182.1 μm 2 /cell) in PPCD-affected eyes, compared with those in PPCD-unaffected eyes from our study subjects ( P < .001 and P = .005, respectively). A statistically significant percent loss in ECD from initial to 3 years was noted in the PPCD-affected eyes ( P = .03). Conclusions: The awareness and treatment of refractive error are important, especially in children with early-onset PPCD during the reversible period of amblyopia. Long-term monitoring of corneal endothelium is required in pediatric patients with early-onset PPCD based on a significant endothelial loss over 3 years in PPCD-affected eyes.